2017
DOI: 10.1155/2017/6241479
|View full text |Cite
|
Sign up to set email alerts
|

Permanent Deformation Characteristics of Coarse Grained Subgrade Soils under Train-Induced Repeated Load

Abstract: This paper presents the results of a laboratory experiment that aimed to characterize the permanent deformation behavior of coarse grained soils. To evaluate the effects of the cyclic stress amplitude, initial mean stress, and initial stress ratio on the permanent axial deformation, six series of repeated load triaxial tests were performed. The results indicate that permanent deformation of coarse grained soils increased with increasing cyclic stress amplitude. In particular, for relative low cyclic stress lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…The model define the ratio as the relationship between deviatoric stress and deviatoric stress at failure (q/qf) because the deviatoric stress is supposed to be the most dominating stress component for permanent strains (Li and Selig, 1996, Chai and Miura, 2002, Korkiala-Tanttu, 2005, Chow et al, 2014, Xiao et al, 2015, Yesufa and Hoffa, 2015, Gu et al, 2016. The model developed by Gidel et al (2001) Subsequently, there have been several models including the influence of initial stress indirectly and explicitly (Chai and Miura, 2002, Ling et al, 2017, Wei et al, 2017) that can explain the apparent decrease of permanent deformation as the initial mean stress increases. Put simply, a higher initial stress leads to a greater distance to the failure criterion which then leads to a lower value of permanent deformation.…”
Section: Complexitymentioning
confidence: 99%
See 1 more Smart Citation
“…The model define the ratio as the relationship between deviatoric stress and deviatoric stress at failure (q/qf) because the deviatoric stress is supposed to be the most dominating stress component for permanent strains (Li and Selig, 1996, Chai and Miura, 2002, Korkiala-Tanttu, 2005, Chow et al, 2014, Xiao et al, 2015, Yesufa and Hoffa, 2015, Gu et al, 2016. The model developed by Gidel et al (2001) Subsequently, there have been several models including the influence of initial stress indirectly and explicitly (Chai and Miura, 2002, Ling et al, 2017, Wei et al, 2017) that can explain the apparent decrease of permanent deformation as the initial mean stress increases. Put simply, a higher initial stress leads to a greater distance to the failure criterion which then leads to a lower value of permanent deformation.…”
Section: Complexitymentioning
confidence: 99%
“…The behaviour of geomaterials under cyclic loads can be characterised by either using complex elastoplastic models (recoverable and permanent deformation are both considered) or by shakedown theory and mechanistic-empirical models (Hornych and Abd, 2004). The elastoplastic models, however, despite their ability to accurately predict permanent deformation (the loading history is considered because the equation is solved based on incremental steps), they are difficult to implement, time consuming, and complex (Ling et al, 2017). Most of these models only consider a low number of load cycles, which is not in accordance with the in situ conditions where the number of loads is up to million cycles.…”
mentioning
confidence: 99%
“…It has the characteristics of complex geological origin, diverse composition, and extremely uneven soil and rock particles across multiple orders of magnitude scales and structures [1][2][3][4]. Because soil-rock mixture is easy to get, it is often used for roadbed filling in construction [5].…”
Section: Introductionmentioning
confidence: 99%
“…It demonstrated that as the modulus of elasticity of the soft subsoil of the embankment and the new embankment increased, the largest embankment settlements decreased significantly [6]. Research at the Chinese Academy of Sciences focused on the opposite boundary conditions, by monitoring the permanent deformation characteristics of non-cohesive soils in the subsoil of the embankment [7]. In the conditions of the Slovak Republic, the problem of low deformation-resistant subsoil and embankment construction has been studied and reported in [8].…”
Section: Introductionmentioning
confidence: 99%